A comparative analysis of time averaging for bivalves and brachiopods from a modern tropical shelf - Krause R.A, Jr.; Barbourl-Wood, S. L.; Wehmiller, J. F.; Kowalewski, M.; Simoes, M. G. (Geological Society of America, Abstracts with Programs, 2004)
36(5):383
id: 718